Biotechnological approaches in food adulterants - Verma, Madan L., 1980- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
The book highlights the biotechnological advancement in the area of food adulterants and outlines the current state of art technologies in the detection of food adulterants using omics and nanobiotechnology. The book provides insights to the most recent innovations, trends, concerns, and challenges in food adulterants. It identifies key research topics and practical applications of modern cutting-edge technologies employed for detection of food adulterants including: expansion of food adulterants market, potential toxicity of food adulterants and the prevention of food adulteration act, cutting-edge technology for food adulterants detection, and biosensing and nanobiosensing based detection of food adulterants. There is need for new resources in omics technologies for the application of new nanobiotechnology. Biotechnological Approaches in Food Adulterants provides an overview of the contributions of food safety and the most up-to-date advances in omics and nanobiotechnology approaches to a diverse audience from postgraduate students to researchers in biochemical engineering, biotechnology, food technologist, environmental technologists, and pharmaceutical professionals.
OCLC-licensed vendor bibliographic record.
Keywords: Food adulteration and inspection; Food -- Biotechnology; TECHNOLOGY / Food Science